A Novel Approach: Investigating the Intracellular Clearance Mechanism of Glyceraldehyde-Derived Advanced Glycation End-Products Using the Artificial Checkpoint Kinase 1 d270KD Mutant as a Substrate Model - Kenji Takeda; Akiko Sakai-Sakasai; Kouji Kajinami; Masayoshi Takeuchi (Cells, 2023)
Advanced glycation end-products (AGEs), formed through glyceraldehyde (GA) as an intermediate in non-enzymatic reactions with intracellular proteins, are cytotoxic and have been implicated in the pathogenesis of various diseases. Despite their significance, the mechanisms underlying the degradation of GA-derived AGEs (GA-AGEs) remain unclear. In the present study, we found that N-terminal checkpoint kinase 1 cleavage products (CHK1-CPs) and their mimic protein, d270WT, were degraded intracellularly post-GA exposure. Notably, a kinase-dead d270WT variant (d270KD) underwent rapid GA-induced degradation, primarily via the ubiquitin–proteasome pathway. The high-molecular-weight complexes formed by the GA stimulation of d270KD were abundant in the RIPA-insoluble fraction, which also contained high levels of GA-AGEs. Immunoprecipitation experiments indicated that the high-molecular-weight complexes of d270KD were modified by GA-AGEs and that p62/SQSTM1 was one of its components. The knockdown of p62 or treatment with chloroquine reduced the amount of high-molecular-weight complexes in the RIPA-insoluble fraction, indicating its involvement in the formation of GA-AGE aggregates. The present results suggest that the ubiquitin–proteasome pathway and p62 play a role in the degradation and aggregation of intracellular GA-AGEs. This study provides novel insights into the mechanisms underlying GA-AGE metabolism and may lead to the development of novel therapeutic strategies for diseases associated with the accumulation of GA-AGEs.